Text-messaging program improves outcomes in outpatient cardiovascular rehabilitation. (1st June 2015) - Lounsbury, Patricia; Elokda, Ahmed S.; Gylten, Darin; Arena, Ross; Clarke, William; Gordon, Ellen E.I.
Abstract: Background: Outpatient cardiac rehabilitation (OP-CR) is a highly beneficial program but vastly under utilized. Methods: The efficacy of a text-messaging program was analyzed to determine if implementation could improve number of OP-CR sessions completed. All patients enrolled in OP-CR from July 2011 through December 2012 were invited to join a text-messaging program on their first visit. The program required that the patient possesses a cell phone with texting capabilities. Participants received three to five text-messages per week offering heart-healthy tips and requests for body weight, minutes of exercise, blood pressure, and medication adherence. Patients enrolled (n = 52) in the texting program (Tx) were compared with those who were not (n = 185) (NTx) in several clinical indices and were compared using matched pairs (same subjects), comparison of means and frequencies, chi-square statistics, t -tests, and the Wilcoxon Rank Sum test. Results: Significantly more patients in the Tx group completed the OP-CR program (61.5% versus 50%, p  = 0.01). For those completing OP-CR, subjects in the Tx group completed significantly more sessions (31.4) than the NTx group (25.3) ( p  = 0.01). Additionally, significantly more in the Tx group were younger than those in the Ntx group. Conclusions: Patients enrolled in OP-CR who participated in a text-messaging program were younger, attended significantly more sessions and were significantly more likely to complete the program.